Software Engineering Competency Challenges - Souza, Adriana Silveira de; Oliveira, Juliano Lopes de; Paiva, Sofia Larissa da Costa; Vasconcelos, Alexandre Marcos Lins de (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES), 2024)
Context: Competent practitioners are the most critical factor in accomplishing Software Engineering’s (SE) purpose of building and sustaining high-quality software. Challenges: The demand for competent SE professionals grows faster than academia and industry’s capacity to teach and develop these professionals. There is a discrepancy between the competencies obtained by SE graduates and those required by different domains of the software industry. Conflicts and misuse of SE competency elements and concepts hinder cooperation in the SE community. The simplistic view of human factors related to SE competency hampers its application in SE education, research, and industry communities. Implications: A profound and consensual understanding of SE competency can accelerate SE professionals’ training and direct them to meet the software industry’s needs. Theories and practices based on a uniform construct can improve software quality and increase teams’ productivity.